O Cretácico na região de Queluz : património natural em torno da escola - Guerra, Maria de Fátima Ferreira (2011)
Com este trabalho pretendeu-se planear e levar a cabo um conjunto de actividades no âmbito da Geologia, passíveis de serem desenvolvidas em vários ambientes de aprendizagem - campo, sala de aula, laboratório e computador - que permitam aos alunos conhecer a litologia e a história geológica da zona onde vivem. A investigação realizada, as actividades e materiais elaborados centraram-se numa zona de cerca de 3-4 Km em volta da Escola Secundária Stuart Carvalhais, em Massamá (Queluz), nos arredores de Lisboa. A escolha deste tema e desta área pretende proporcionar aos alunos a realização de trabalho de campo, em alternativa às visitas de estudo tradicionais, levando-os a terem novas visões da Geologia e do local em que vivem, de modo a compreenderem que o chão que pisam tem uma longa história para contar. O trabalho iniciou-se com o reconhecimento da Geologia local com base na cartografia existente, no trabalho de campo e na bibliografia disponível. Seleccionaram-se os afloramentos que pareceram mais adequados e foram recolhidos dados relativos à litologia, aos recursos, ao património natural e arqueológico, à ocupação antrópica da região e aos problemas de Ordenamento. Em simultâneo procedeu-se à revisão bibliográfica relativa às perspectivas actuais da Educação em Ciências, às Orientações Curriculares relativas aos 7º, 10º e 11º anos, das disciplinas de Ciências Naturais e Biologia e Geologia, e ao Projecto Educativo da Escola - “Stuart XXI” - com vista à contextualização didáctica das actividades a desenvolver. Da investigação resultou a planificação de um conjunto de actividades para cada um dos anos de escolaridade referidos. Por existirem nas imediações da escola excelentes afloramentos e uma grande variedade de aspectos geológicos com potencialidades didácticas, as actividades que se propõem não esgotam as possibilidades que a zona proporciona. Os percursos foram escolhidos em função da sua extensão e segurança e as actividades foram planificadas em função dos conteúdos a leccionar e do grau de dificuldade exigido para os diferentes anos de escolaridade. As actividades planeadas encontram-se em anexo. ABSTRACT: The main objective of this work was the conceptual development, planning and design of a geology outreach project to be performed both inside and outside the classroom (field, laboratory, computer room). The approach followed is expected to contribute to motivate the students to the study of the geology of the place where they live and to increase their interest in earth sciences. The region under investigation is located in the southern sector of the West Portuguese Mesozoic Basin (Lusitanian Basin) and involves an area of 3-4 km around the Stuart Carvalhais Secondary School in Massamá (Queluz), in the environments of Lisbon. The area and the topics selected will provide an opportunity to carry out field work, in alternative to traditional field trips and will help the students to develop a new perspective of Geology. In the first stage of the project, the students will look at topographic and geologic maps in order to identify the main geologic units cropping out in the region. Additional information will be obtained through bibliographic and internet research. Problems such as land management, natural resources and human occupation will also be focused. The field trip, consisting of five selected stops, provides an opportunity to observe good outcrops of sedimentary and igneous rocks of Cretaceous age and to collect a varied set of field data, based on which it will be possible to reconstruct the geological history of the region. On the walk, the rock-forming processes as well as the natural and historical patrimony will be discussed and some information on geotectonic setting will be given. Back to school, the students will compile all the field observations, will do some further research in the laboratory and will integrate and present the results obtained. The project is designed for students of Earth Sciences of the 7Th grade and of Biology and Geology of the 10th and 11th grade and follows the curricular recommendations of the Portuguese Ministry of Education for these levels of teaching. It also reflects the concerns of the Education Project of the School - “Stuart XXI”. The thesis is organized in six chapters. The main objectives of the work and the adopted methodology are presented in the first chapter. Chapter II describes the area around the school, whilst Chapter III includes the guide of the geologic tour with a detailed description of the different stops. Chapter IV provides a literature review of the main aspects of the Geology of the Cretaceous in Portugal. Chapter V presents a brief overview of the geodynamic evolution of the Lusitanian Basin and Chapter VI includes the main conclusions of the thesis.